Climate Change in Kenya: Understanding Major Threats and Government Policies for Resilience - (:unkn) unknown (My University, 2023)
This article aims to describe and highlight major climate threats found in Kenya and climate change policy implemented by the government of Kenya from 2010 to 2022. Climate change poses a severe threat to the living conditions of citizens and wildlife worldwide. Numerous studies have demonstrated that in the absence of implemented policies, living conditions can be further deteriorated. While Africa may not contribute significantly to air pollution, there are other human activities that pollute the environment and need to be eliminated, as African people are already suffering from the impacts of climate change. African countries must take necessary steps to initiate sustainable development policies that ensure a better life for their citizens. In the case of Kenya, droughts and floods have resulted in the loss of human and animal lives and have negatively impacted the country's economy. Consequently, the government has implemented necessary measures since 2010 to address the issue of climate change. Various policies such as the National Climate Change Response Strategy (2010), the National Environment Policy (2013), Kenya National Adaptation Plan 2015-2030, Climate Change Bill (2014), National Climate Change Action Plan (NCCAP 2013-2017), National Climate Change Action Plan (2018-2022), and National Drought Management Authority (2016) have been enacted in response to climate change. These policies demonstrate the government's genuine concern for climate change issues. Overall, this study aims to contribute to the understanding of climate change policy in Kenya and raise awareness about the global threat posed by climate change.
Keywords: African Research